2014
DOI: 10.1017/s0043933914000348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci and candidate genes for the economic traits in meat-type chicken

Abstract: Recent progress has been achieved in the identification of quantitative trait loci (QTLs) and candidate genes, and they have been found to be very important for the production of chickens with more desirable meat characteristics. The major economic traits of chicken meat production were divided into two major categories, namely growth and carcass condition. In this paper, the QTL locations and candidate genes for the above mentioned traits are reviewed. The results presented here will provide guidelines for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Meat quality traits have important economic value and are considered to be complex quantitative traits controlled by multiple genes ( Cahyadi et al, 2014 ). For example, many previous studies have shown that the fatty acid binding protein ( FABP ) gene plays an important role in improving overall meat quality ( Cho et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meat quality traits have important economic value and are considered to be complex quantitative traits controlled by multiple genes ( Cahyadi et al, 2014 ). For example, many previous studies have shown that the fatty acid binding protein ( FABP ) gene plays an important role in improving overall meat quality ( Cho et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Carcass traits can be affected by genetics, feed, and environment ( Mansour and Hosna, 2010 ; Cahyadi et al., 2014 ; Arowolo et al., 2019 ). Meat quality is important for consumers and product processing and can be influenced by genetics, age, sex, feed, and management ( Fletcher, 2002 ; Frizzell et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other QTL regions were also identified on GGA4 for overall body weight, CW wing weight, drum stick weight, and thigh weight ( Ikeobi et al, 2004 ; Schreiweis et al, 2005 ; Tsudzuki et al, 2007 ). Therefore, along with GGA1, GGA4 is implicated as a chromosome that harbors QTLs for growth-related traits ( Cahyadi et al, 2014 ). Regarding the QTLs for CW in KNC, two QTLs were located at 0 and 70 cM on GGA19.…”
Section: Discussionmentioning
confidence: 99%